(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Artificial Intelligence (AI) is transforming medicine and medical education by providing novel opportunities to enhance clinical outcomes, improve diagnostic tools, and refine instructional methodologies. Nonetheless, its swift incorporation presents considerable ethical, legal, and practical issues. This study investigates the advantageous applications and possible hazards of AI in healthcare, concentrating on its function in clinical practice, patient care, and medical education. It offers a comprehensive perspective on AI’s present and future influence in the medical domain, emphasizing avenues for advancement and approaches to alleviate associated concerns. The results underscore the necessity for prudent AI deployment and continuous investigation to tackle related issues.